Windows on Christmas - Crowder, Bill. (Grand Rapids, MI : Discovery House Publishers ; Uhrichsville, Ohio : Distributed to the trade by Barbour Publishing, Inc., 2007)
A different perspective can revolutionize our appreciation of the familiar. This is what Bill Crowder does as he examines the familiar story of the birth of Christ in the gospel of Luke. By looking through the windows provided by those who were there--Mary and Joseph, the angels and the shepherds, Simeon and Anna-we see and feel what they saw and felt, and learn from their responses. As we enter into the nativity events that altered the world forever and as we join the humble worshipers who welcomed Christ at His birth, we get what we need most-fresh perspective.
Keywords: Jesus Christ -- Nativity; Christmas; Jesus Christ; Christmas; Nativity of Jesus Christ